Induction of Endoplasmic Reticulum Stress by CdhM Mediates Apoptosis of Macrophage During Mycobacterium tuberculosis Infection - Xu, Peng; Tang, Jing; He, Zheng-Guo (Frontiers in Cellular and Infection Microbiology, 2022)
The normal operation of the endoplasmic reticulum (ER) is critical for cells and organisms. But ER stress, caused by imbalanced protein-folding, occurs frequently, which will perturb the function of the ER and even results in cell apoptosis eventually. Many insults can induce ER stress, pathogens infection is one of them. Most of the genes involved in ER stress have been reported to be upregulated in Mycobacterium tuberculosis (Mtb) granulomas of humans and mice, implicating that infection with Mtb can induce ER stress. However, little is known about the molecular mechanism of Mtb induction of ER stress. Here, we reveal that mycobacterium protein CdhM could target the ER and cause obvious ER expansion and cell death. RNA-seq analysis suggests that most of the ER stress-involved genes were modulated by CdhM. Further assessed by biochemical experiments, the transcription and protein levels of ER stress markers BiP and CHOP, as well as the levels of XBP1 splicing and eIF2α phosphorylation were significantly increased by CdhM, confirmed that CdhM could induce ER stress alone or during infection. A single conserved amino acid mutant of CdhM, including L44A, G96A, H150A or W175A, was incapable of inducing ER stress, which indicates that induction of ER stress by CdhM is specific and functional. Furthermore, CdhM-induced ER stress could also promote apoptosis of macrophages during Mtb infection. Overexpression of CdhM conferred a significant benefit for Mtb replication by releasing Mtb into extracellular during infection of macrophage in vitro, as presented in CFU assays. Overall, our study identified a novel Mtb effector protein CdhM which may promote Mtb dissemination and proliferation by induction of ER stress and apoptosis and provided new insight into the physiological significance of induction of ER stress in tuberculosis (TB) granulomas.